2016
DOI: 10.1016/j.jsxm.2016.02.171
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Continuous Dosing of Tadalafil Once Daily vs Tadalafil On Demand in Clinical Subgroups of Men with Erectile Dysfunction: A Descriptive Comparison Using the Integrated Tadalafil Databases

Abstract: Introduction Various factors play a role in the development of erectile dysfunction (ED). Aim To provide a descriptive comparison of erectile function response for tadalafil on-demand (PRN) and once-daily (OAD) dosing regimens in patients with common comorbid conditions, treatments, or risk factors that can be considered when treating ED. Methods In total, 17 PRN and 4 OAD placebo-controlled studies were included in the integrated database in these pooled analyses. Data were analyzed from patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Due to the lack of reference on the expected effect size of using CHSGS to treat erectile dysfunction evaluated in this study, we did not estimate the sample size based on a power calculation. According to previous studies, International Index of Erectile Function 5 (IIEF-5) scores of ED patients increased 6.0-7.1 after tadalafil [13,15]. Therefore, we predicted ascension of IIEF-5 score by 6.5 points after oral tadalafil or CHSGS capsule, a reduction by 2.5 points after placebo.…”
Section: Sample Sizementioning
confidence: 75%
See 1 more Smart Citation
“…Due to the lack of reference on the expected effect size of using CHSGS to treat erectile dysfunction evaluated in this study, we did not estimate the sample size based on a power calculation. According to previous studies, International Index of Erectile Function 5 (IIEF-5) scores of ED patients increased 6.0-7.1 after tadalafil [13,15]. Therefore, we predicted ascension of IIEF-5 score by 6.5 points after oral tadalafil or CHSGS capsule, a reduction by 2.5 points after placebo.…”
Section: Sample Sizementioning
confidence: 75%
“…According to the current guidelines, tadalafil [9][10][11][12][13][14][15][16] is the first-line oral pharmacotherapy for ED. It could take action from various species in vivo and in vitro by increasing the intracellular concentrations of cGMP by amplifying the endogenous NO-cGMP pathway [9,17].…”
Section: Introductionmentioning
confidence: 99%
“…Five meta-analyses have compared on-demand vs. daily tadalafil and the findings are reported in Table 2. Brock et al [39] compared only RCTs and concluded equal efficacy but these trials were usually of 12-week duration where on-demand patients were provided with unlimited medication such that total dose of tadalafil was usually significantly higher than 5 mg daily dosing. Bansal et al [40] reviewed 6 head to head studies of up to 12 weeks and concluded that daily tadalafil resulted in a 1.82 higher ED score then 20mg on-demand.…”
Section: The Case For Tadalafil 5 Mg Daily For Erectile Dysfunction Imentioning
confidence: 99%
“…Курсовая терапия ежедневного приема ингибиторов ФДЭ-5 представляет высокий интерес в лечении пациентов, у которых прием этих препаратов "по требованию" неэффективен или малоэффективен. Как показывает статистика, количество таких пациентов достигает 30-40% [17]. Постоянный прием ингибиторов ФДЭ-5 может рассматриваться в качестве дополнительной возможности улучшить ЭФ в группе "тяжелых для лечения" пациентов: больных сахарным диабетом и пациентов, перенесших радикальную простатэктомию [18].…”
unclassified